1999
DOI: 10.1152/jappl.1999.86.3.852
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-related, muscle-specific changes in protein metabolism and fiber type profile after faba bean intake

Abstract: Male growing Wistar rats were fed, over 15 days, isoenergetic (16.72 +/- 0.49 MJ) and isoproteic (11%) diets containing either lactalbumin or raw Vicia faba L. (Vf) as the sole source of protein. Compared with pair-fed controls (PF), soleus muscles of Vf-fed rats showed increased (P < 0.05) synthesis and breakdown rates. In addition, the soleus of Vf-fed rats displayed a decrease (P < 0.05) in type I and an increase (P < 0.01) in type IIc fibers compared with that of PF animals. On the contrary, extensor digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…However, the effect of legume feeding on DNA levels seems to depend on the metabolic type of muscle since they were signifi cantly lower in gastrocnemius muscle (fast-twitch oxidative glycolytic) of the bean-or lentil-fed rats than in the controls, but this did not occur in the soleus muscle (slow oxidative muscle). A similar difference in the responses of different metabolic types of muscles to legume feeding has already been observed for protein and RNA contents when comparing the effects of raw Vicia faba feeding on soleus and on extensor digitorum longus (fast-twitch glycolytic) muscles in rats [42] . In that experiment, the difference between muscle responses was related to modifi cations of the muscle fi bre composition that appeared to be induced by hormonal changes resulting from legume feeding.…”
Section: Discussionsupporting
confidence: 74%
“…However, the effect of legume feeding on DNA levels seems to depend on the metabolic type of muscle since they were signifi cantly lower in gastrocnemius muscle (fast-twitch oxidative glycolytic) of the bean-or lentil-fed rats than in the controls, but this did not occur in the soleus muscle (slow oxidative muscle). A similar difference in the responses of different metabolic types of muscles to legume feeding has already been observed for protein and RNA contents when comparing the effects of raw Vicia faba feeding on soleus and on extensor digitorum longus (fast-twitch glycolytic) muscles in rats [42] . In that experiment, the difference between muscle responses was related to modifi cations of the muscle fi bre composition that appeared to be induced by hormonal changes resulting from legume feeding.…”
Section: Discussionsupporting
confidence: 74%
“…It has been also reported that bean constituents infl uence and modulate the endocrine status [21] , which can change protein metabolism. Frühbeck et al [41] showed that plasma glucagon levels increased in rats fed diets containing V. faba and that there were signifi cant negative correlations between glucagon concentration and muscle protein content as well as fractional protein synthesis rate. Also the other hormones (T 3 , T 4 , insulin, corticosterone) were affected by inclusion of V. faba [41] or raw and extruded peas [35] in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Frühbeck et al [41] showed that plasma glucagon levels increased in rats fed diets containing V. faba and that there were signifi cant negative correlations between glucagon concentration and muscle protein content as well as fractional protein synthesis rate. Also the other hormones (T 3 , T 4 , insulin, corticosterone) were affected by inclusion of V. faba [41] or raw and extruded peas [35] in the diet. However, those differences were abolished after supplementation of the diets with amino acids, except for corticosterone, which remained high [35] .…”
Section: Discussionmentioning
confidence: 99%
“…In liver, raw faba bean intake increased protein synthesis in rats [20] whereas enteral infusion of soybean protein decreased it in pigs [19]. Raw faba bean intake decreased protein synthesis rate in gastrocnemius [20], had no effect on extensor digitorum longus and increased it in soleus [21]. Enteral infusion of soybean protein resulted in higher aminoacid uptake by hind legs in pigs than casein infusion [19].…”
Section: Discussionmentioning
confidence: 99%